Shakespeare and the origins of English - Rhodes, Neil, 1953-; Oxford eBooks (Oxford : Oxford University Press, 2004)
What did Shakespeare learn at school? Did he study creative writing? This book addresses these and similar questions as the author shows where the modern subject of 'English' came from and what part Shakespeare played in its formation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Shakespeare, William, -- 1564-1616 -- Influence; Shakespeare, William, -- 1564-1616 -- Study and teaching; English philology -- Study and teaching -- History; English language -- Early modern, 1500-1700.; Electronic books